Assessment of the Physiochemical Characteristics of Water Samples from Vicinity Area of Wadafiae Landfill, Khartoum North, Sudan - Elamin, Omer Abbass; Elhassan, Abdelelah Mohamed; Abdelgadir, Abdelgadir Elfadil; Ahmed, Mariam Hamdan (Tropical Aquatic and Soil Pollution, 2023)
The rapid increase in population, urbanization, industrialization, and changes in consumption patterns have given rise to many environmental problems, which mainly include air, land, and water pollution. In Khartoum North, Khartoum State, Sudan, there was a lack of a compatible solid waste management system. These resulted in a decline in environmental health, and the majority of the yards were turned into dumps (kusha). The current study focused on the effects of uncontrolled dumping of municipal solid waste on groundwater, as well as assessing the risk of physiochemical concentrations in the water around the dumpsite and comparing the differences between the dry and rainy seasons in water samples at Wadafiea Dumpsite, Khartoum North, Sudan. Water parameters such as TSS, Cl, TDS, Ca, Mg, SAR, and Na exceeded the controlled 1 (1.333) and 2 (1.332) levels of water and was within the Sudanese Maximum Values, the bounds of Canadian Guideline Values, and WHO Values.